Joint Association of Low Vitamin K1 and D Status With First Stroke in General Hypertensive Adults: Results From the China Stroke Primary Prevention Trial (CSPPT) - Wei, Yaping; Ma, Hai; Xu, Benjamin; Wang, Zhuo; He, Qiangqiang; Liu, Lishun; Zhou, Ziyi; Song, Yun; Chen, Ping; Li, Jianping; Zhang, Yan; Mao, Guangyun; et al. (Frontiers in Neurology, 2022)
Background: Vitamin K plays a role in preventing vascular calcification and may have a synergetic influence with vitamin D on cardiovascular health. However, whether this relationship applies to stroke, especially in a high-risk population of hypertensive individuals, remains unclear. The present study aims to study the joint association of low vitamin K1 and D status with first stroke in general hypertensive adults. Methods: This study used a nested, case–control design with data from the China Stroke Primary Prevention Trial. The analysis included 604 first total stroke patients and 604 matched controls from a Chinese population with hypertension. Odds ratios (ORs) and 95% confidence intervals were calculated using conditional logistic regression. Results: There was a non-linear negative association between plasma vitamin K1 and the risk of first total stroke or ischemic stroke in the enalapril-only group. Compared to participants in vitamin K1 quartile 1, a significantly lower risk of total stroke (OR=0.58, 95% CI: 0.36,0.91, P=0.020) or ischemic stroke (OR=0.34, 95% CI: 0.17, 0.63, P<0.001) was found in participants in vitamin K1 quartile 2-4 in the enalapril-only group. When further divided into four subgroups by 25(OH)D and vitamin K1, a significantly higher risk of total stroke or ischemic stroke was observed in participants with both low vitamin K1 and 25(OH)D compared to those with both high vitamin K1 and 25(OH)D in the enalapril-only group. No increased risk was observed in the groups low in one vitamin only. Conclusion: Low concentrations of both vitamin K1 and 25(OH)D were associated with increased risk of stroke.